The relationships between communication management and coach-athlete relationship among sport team athletes in Perlis - Ellail Ain Mohd Aznan,; Muhamad Faidhi Baseri,; Mohd Nor Shahizan Ali, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Communication management may encourage the self-confidence in an individual and it will also lead to the closeness or bonding between coaches and athletes. In addition, communication management is also believed will help in increasing the ability and preparedness upon the athletes for each game and competition. Nowadays, coach-athlete relationship had becoming outrageous studies as past study shows that despite having good relationship, it may also help in reducing stress, and conflict among them, not only that it can also enhance their athletes’ satisfaction and reduce burn out. It was proven that coach-athlete relationship is very important in creating a positive environment around the coach and players. This study focused on the communication management and coach-athlete relationship among the team sport athlete in Perlis. A total of 100 questionnaires were distributed. The data collected were analyzed using the Statistical Package for the Social Science (SPSS) version 22. Pearson correlation was used in determining the relationship between communication management and coach-athlete relationship. The results proved that there was a significant between communication management and coach-athlete relationship. It was suggested that for future studies, the study could focus on identifying the mediating factors that influence the relationship between communication management and coach-athlete relationship.